Preclinical Studies of Canagliflozin, a Sodium-Glucose Co-Transporter 2 Inhibitor, and Donepezil Combined Therapy in Alzheimer's Disease - Gabriela Dumitrita Stanciu; Daniela Carmen Ababei; Carmen Solcan; Veronica Bild; Andrei Ciobica; Sorin-Ioan Beschea Chiriac; Loredana Maria Ciobanu; Bogdan-Ionel Tamba (MDPI AG, 2023)
The incidence of neurodegenerative diseases, such as Alzheimer's disease (AD), is continuously growing worldwide, which leads to a heavy economic and societal burden. The lack of a safe and effective causal therapy in cognitive decline is an aggravating factor and requires investigations into the repurposing of commonly used drugs. Sodium-glucose co-transporter 2 inhibitors (SGLT2i) are a new and efficient class of hypoglycemic drugs and, due to their pleiotropic effects, have indications that go beyond diabetes. There is emerging data from murine studies that SGLT2i can cross the blood-brain barrier and may have neuroprotective effects, such as increasing the brain-derived neurotrophic factor (BDNF), reducing the amyloid burden, inhibiting acetylcholinesterase (AChE) and restoring the circadian rhythm in the mammalian target of rapamycin (mTOR) activation. The current study investigates the effect of an SGLT2i and donepezil, under a separate or combined 21-day treatment on AD-relevant behaviors and brain pathology in mice. The SGLT2i canagliflozin was found to significantly improve the novelty preference index and the percentage of time spent in the open arms of the maze in the novel object recognition and elevated plus maze test, respectively. In addition, canagliflozin therapy decreased AChE activity, mTOR and glial fibrillary acidic protein expression. The results also recorded the acetylcholine M1 receptor in canagliflozin-treated mice compared to the scopolamine group. In the hippocampus, the SGLT2i canagliflozin reduced the microgliosis and astrogliosis in males, but not in female mice. These findings emphasize the value of SGLT2i in clinical practice. By inhibiting AChE activity, canagliflozin represents a compound that resembles AD-registered therapies in this respect, supporting the need for further evaluation in dementia clinical trials.